THE BASIC INTELLECTUAL OF VAGIF BAYATLI ODER’S POETRYPARADOXES AS ONE OF HIS ARTISTIC CHARACTERISTICS (TAMADDUN NURI JURNALI, 2024)
The article «Paradoxes as one of the main idea-artistic features of Vagif Bayatli Oder’s poetry» can be conventionally divided into two parts: in the first part, which is a theoretical introduction to the topic, the concept of paradox in general, its origin and essence, historical development, main features, types and other issues are discussed. In the second part, the literary-artistic and socio-political sources, main types, and syntactic types of paradox in the poetry of V.B.Oder are clarified. The author examines the main subject of research against the background of world and national scientific-philosophical, literary-artistic thought, shows its connection with time and life, generally speaking, evaluates the paradoxes in the poet’s work as a cognitive strategic method in the search for truth.